In DNA We Trust?: Biolegal Governmentality and Illegal Logging in Contemporary Indonesia. Issue 1 (1st March 2017) - Budiastuti, Arum
Abstract : In this article the author scrutinizes the application of a novel genetic technology within the context of the timber industry in Indonesia, a country suffering massive deforestation at the rate of 2.8 million hectares every year. It starts by providing a brief description of Doublehelix Tracking Technologies, the first timber accreditation body that uses DNA testing to ensure that the timber procured is from a "known" origin. The article also discusses the historical overview of the various schemes of timber verification practices from the New Order era up to the present day, providing the context in which the third-party verification technology emerges. Data were sourced from public documents and interviews. Drawing on concepts of governmentality and biolegality within Andrew Barry's framework of "technological society, " the author argues that Doublehelix constructs the sense and the importance of DNA technology as "the best possible governor" of timber logging in Indonesia and the problem of transnational timber smuggling. Moreover, the biolegal practice of the technology is revealed in the way it challenges the existing definitions of legality/illegality and constructs identities. Not only does it modify the governmental target (from a set of practices to the materiality of timber), it also creates identities of the timber, that is, which timber meets the criteria to be procured and which timber is of "unknown" origin and subject to further surveillance.